Schaum's outlines strength of materials - Nash, William; Potter, Merle C. (New York : McGraw Hill Education, 2011)
This ideal review for the thousands of civil and mechanical engineering students covers tension and compression, shearing forces, torsion, and more.
1. Tension and Compression -- 2. Statically Indeterminate Force Systems. Tension and Compression -- 3. Thin-Walled Pressure Vessels -- 4. Direct Shear Stresses -- 5. Torsion -- 6. Shearing Force and Bending Moment -- 7. Centroids, Moments of Inertia, and Products of Inertia of Plane Areas -- 8. Stresses in Beams -- 9. Elastic Deflection of Beams: Double-Integration Method -- 10. Elastic Deflection of Beams: Method of Singularity Functions -- 11. Statically Indeterminate Elastic Beams -- 12. Special topics in Elastic Beam Theory -- 13. Plastic Deformations of Beams -- 14. Columns -- 15. Strain Energy Methods -- 16. Combined Stresses -- 17. Members Subject to Combined Loadings; Theories of Failure
Includes index.
Keywords: STRENGTH OF MATERIALS